Influence of Drill Method in Improving Basic Cosmetology Skills of Deaf Children in Special School - Anelia Muanis; Toni Yudha Pratama; Reza Febri Abadi; Yuni Tanjung Utami (Journal of Disability, 2021)
This research is an experimental study with a quantitative approach with the design of One Group Pre-test and Post-test. This study aims to find out the influence of drill methods in improving basic cosmetology skills in deaf children. The subjects used in this study were deaf students of SMPLB class VII in SKh Negeri 02 Kota Serang which amounted to 4 people. Based on the results of inferesial statistical analysis using the wilcoxon test formula (t) indicates that Tcalculate = 0 and based on the critical value for the wilcoxon test at the significance level of 0.05 with the sum N < 7, obtained Ttable = 0, then H0 is rejected because Tcalculate = Ttable This means that the hypothesis proposed in this study is accepted. This shows that the drill method is influential in improving the basic makeup of deaf children in SKh Negeri 02 Serang City.